2018
DOI: 10.1155/2018/1082076
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Epithelial Cells Accelerate Diabetic Wound Healing by Modulating Inflammation and Promoting Neovascularization

Abstract: Human amniotic epithelial cells (hAECs) are nontumorigenic, highly abundant, and low immunogenic and possess multipotent differentiation ability, which make them become ideal alternative stem cell source for regenerative medicine. Previous studies have demonstrated the therapeutic potential of hAECs in many tissue repairs. However, the therapeutic effect of hAECs on diabetic wound healing is still unknown. In this study, we injected hAECs intradermally around the full-thickness excisional skin wounds of db/db … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…By contrast, treating wounds with FB promotes acceleration of wound healing with the deposition of increased amounts of collagen and fibronectin, and increased numbers of fibroblasts, macrophages and large capillaries. These are typical features of late stages of wound healing (Raekallio and Viljanto, 1983;Pettet et al, 1996;Templin et al, 2009;Suhaeri et al, 2018;Zheng et al, 2018;Opneja et al, 2019). These in vivo wound healing data suggested the presence of healing stimulatory component(s) in the FB preparations, as we have described previously in other wound healing models (Al-Hassan and Criddle, 1982;Al-Hassan et al, 1983;Al-Hassan JM et al, 1985;Al-Hassan et al, 1986;Al-Hassan et al, 1987;Al-Hassan et al, 1991).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…By contrast, treating wounds with FB promotes acceleration of wound healing with the deposition of increased amounts of collagen and fibronectin, and increased numbers of fibroblasts, macrophages and large capillaries. These are typical features of late stages of wound healing (Raekallio and Viljanto, 1983;Pettet et al, 1996;Templin et al, 2009;Suhaeri et al, 2018;Zheng et al, 2018;Opneja et al, 2019). These in vivo wound healing data suggested the presence of healing stimulatory component(s) in the FB preparations, as we have described previously in other wound healing models (Al-Hassan and Criddle, 1982;Al-Hassan et al, 1983;Al-Hassan JM et al, 1985;Al-Hassan et al, 1986;Al-Hassan et al, 1987;Al-Hassan et al, 1991).…”
Section: Discussionsupporting
confidence: 83%
“…Our recent study showed that pure F6 effectively induces neutrophil extracellular trap (NET) formation in human neutrophils (Khan et al, 2018). NETs promote recruitment of neutrophils (Pettet et al, 1996;Templin et al, 2009;Zheng et al, 2018). Although detection of NET formation in zebrafish has not been clearly established, increased local NET formation in the presence of F6 could lead to increased neutrophil recruitment to wound sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported, that when a patient with type I Diabetes mellitus was treated with amniotic cells, the patient remained independent of insulin intake for 6.2 months and later, insulin requirements were readjusted to 8 IU/day post-transplantation compared to 38 IU/day, pre-transplant (73). It was also reported, that hAEC have the potential for wound healing (74), and the correction of heart disease (75), stroke (76) multiple sclerosis (40) and many other diseases (Figure 9).…”
Section: Amnion Epithelial Cell Therapy Of Other Tissuesmentioning
confidence: 99%
“…Based on their plasticity and immunomodulatory properties, hAESCs have been considered for treatment of a broad variety of conditions, including lung fibrosis [ 40 , 115 , 131 , 149 , 151 , 152 , 153 , 154 ], spinal cord injuries [ 60 ], Parkinson’s disease [ 64 ], Alzheimer’s disease [ 155 ], diabetes [ 69 ], wound healing [ 147 , 148 , 156 ], liver fibrosis [ 75 , 157 , 158 , 159 ], autoimmune uveitis [ 135 ], Hashimoto’s thyroiditis and systemic lupus erythematosus [ 134 ], and intrauterine adhesions [ 160 , 161 , 162 ]. Among these preclinical trials involving hAESCs, autoimmune diseases make up a large proportion, presumably because of the tremendous effect of immunomodulation.…”
Section: The Therapeutic Potential and Clinical Advances Of Human mentioning
confidence: 99%